EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PENDEKATAN CTL TERHADAP PRESTASI BELAJAR DAN ASPEK AFEKTIF SISWA DITINJAU DARI KEMAMPUAN SPASIAL SISWA - Habib Ratu Perwira Negara; Tri Atmojo K; Imam Sujadi (Universitas Islam Negeri (UIN) Mataram, 2016)
The current research intends to find out the different effect of the Jigsaw type of cooperative learning model with CTL approach, the Jigsaw type of cooperative learning model without CTL approach, and the direct learning model towards students mathematics learning achievement and affective aspect regarding student spatial ability which is categorized into high, medium and low. The research was quasi experimental. The results of the research were as follows. (1) The cooperative learning model of Jigsaw type with CTL approach and the cooperative learning model of Jigsaw type gaves a better achievement than direct learning model, and the cooperative learning model of Jigsaw type with CTL approach gaves the same achievement as the cooperative learning model of Jigsaw type. (2) The cooperative learning model of Jigsaw type with CTL approach results a better affective effect than the cooperative learning model of Jigsaw type and direct learning model, and the cooperative learning model of Jigsaw type gaves a better achievement than direct learning model. (3) Students with the high spatial ability had better achievement than students with the medium and low spatial ability, and students with the medium spatial ability had better achievement than students with the low spatial ability. (4) Students with the high spatial ability had better affective aspect than students with the medium and low spatial ability, and students with the medium spatial ability had the same affective aspect as students with the the low spatial ability. More findings are elaborated further on the discussion and conclusion part of the current report.